2013
DOI: 10.1530/joe-13-0022
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy with melatonin and dexamethasone in a mouse model of traumatic brain injury

Abstract: Traumatic brain injury (TBI) is a major cause of preventable death and morbidity in young adults. This complex condition is characterized by a significant blood-brain barrier leakage that stems from cerebral ischemia, inflammation, and redox imbalances in the traumatic penumbra of the injured brain. Recovery of function after TBI is partly through neuronal plasticity. In order to test whether combination therapy with melatonin and dexamethasone (DEX) might improve functional recovery, a controlled cortical imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 51 publications
2
54
0
Order By: Relevance
“…The rotarod treadmill (Accuscan, Inc., Columbus, OH) assesses motor balance and coordination. For testing, the animals were subjected to three trials; the average score was used as the individual rotarod score, as previously described (12).…”
Section: Discussionmentioning
confidence: 99%
“…The rotarod treadmill (Accuscan, Inc., Columbus, OH) assesses motor balance and coordination. For testing, the animals were subjected to three trials; the average score was used as the individual rotarod score, as previously described (12).…”
Section: Discussionmentioning
confidence: 99%
“…Pre-clinical studies have found MEL leads to attenuation of one or more of the histopathological and functional consequences of TBI [13,14]. Moreover, published evidence suggests that MEL has many mechanisms of action, including anti-apoptotic [15,16], anti-oxidative [17], and anti-mitophagic [18] properties; notably, the abovementioned pathways are all well-established as implicated in TBI-pathology.…”
Section: Introductionmentioning
confidence: 99%
“…unlike this study many studies have showed synergistic effect of dexamethasone and melatonin in various inflammatory disorders having somewhat same pathophysiology as in sepsis. 39,40 The discrepancy may be due to alteration in this methodology and pathophysiology of LPS induced hepatotoxicity. This study clearly demonstrates that both dexamethasone and melatonin restored LPS induced liver injury in this animal model.…”
Section: Discussionmentioning
confidence: 99%